NARMA-L2 Controller for Five-Area Load Frequency Control - Priyanka Sharma (IAES Indonesian Section, 2014)
This paper investigates the load-frequency control (LFC) based on neural network for improving power system dynamic performance. In this paper an Artificial Neural Network (ANN)based controller is presented for the Load Frequency Control (LFC) of a five area interconnected power system. The controller is adaptive and is based on a nonlinear auto regressive moving average (NARMA-L2) algorithm. The working of the conventional controller and ANN based NARMA L2 controllers is simulated using MATLAB/SIMULINK package.. The Simulink link results of both the controllers are compared.